2015
DOI: 10.1016/j.midw.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

‘What about the mother?’ Women׳s and caregivers׳ perspectives on caesarean birth in a low-resource setting with rising caesarean section rates

Abstract: we raise a concern that women and caregivers might overlook maternal risks with caesarean section for the benefit of the baby, a shift in focus that can have serious consequences on women's health in low-resource settings. Caregivers need to reflect on how they counsel women on caesarean section, as many women perceived a lack of indication for their operations. Supportive attendance by a relative during birth and more comprehensive antenatal care counselling about caesarean section indications and complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 36 publications
6
86
1
Order By: Relevance
“…Second, women's beliefs about the safety of cesarean, either for mother or neonate, seemed to motivate presentation. This finding could be in line with evidence from Sub‐Saharan Africa suggesting that some women avoid deliveries in facilities owing to fear of undergoing a cesarean . Quality improvement at the facility level that can increase TOL rates and the safety of cesarean might encourage women to present earlier if they feel that cesarean is not inevitable once there.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Second, women's beliefs about the safety of cesarean, either for mother or neonate, seemed to motivate presentation. This finding could be in line with evidence from Sub‐Saharan Africa suggesting that some women avoid deliveries in facilities owing to fear of undergoing a cesarean . Quality improvement at the facility level that can increase TOL rates and the safety of cesarean might encourage women to present earlier if they feel that cesarean is not inevitable once there.…”
Section: Discussionsupporting
confidence: 80%
“…This finding could be in line with evidence from Sub-Saharan Africa suggesting that some women avoid deliveries in facilities owing to fear of undergoing a cesarean. 20 Quality improvement at the facility level that can increase TOL rates and the safety of cesarean might encourage women to present earlier if they feel that cesarean is not inevitable once there. For women who are not appropriate candidates for TOL, directed counseling that dispels myths of the impact or safety of cesarean and explains the need should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Women who delivered vaginally might have represented good candidates for a trial of labor, although facilities for such assessments are not the same at MNH as in a facility in a high-income country. Lead time from decision to operate can in this low-income setting be extended by several hours [21], meaning that VDs could represent a group of most urgent cases that did not make the necessary conversion to CD. This might be one explanation for the clustering of VD stillbirths, indicating the difficult conditions prevailing in this setting, especially as the study sample comprised of presumed intrapartal deaths.…”
Section: Discussionmentioning
confidence: 99%
“…At the national referral hospital in Tanzania, obstructed labour contributes up to 3% of maternal deaths [16]. In the same setting, recent cross-sectional [23,24] and qualitative studies [25,26] have revealed a significant number of questionable decisions in the case of caesarean sections (CS), delayed pre-operative interventions, too few assisted vaginal deliveries, and inadequate use of partograms as the main reasons for substandard obstetric care. Since half of the CS that were performed were due to obstructed labour (MNH database 2014, unpublished report), then it was important to evaluate and improve standards of diagnosis and management of obstructed labour.…”
Section: Introductionmentioning
confidence: 99%